2012
DOI: 10.1124/mol.111.076216
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Peroxisome Proliferator-Activated Receptor γ Activation by Luteolin

Abstract: The peroxisome proliferator-activated receptor ␥ (PPAR␥) is a target for treatment of type II diabetes and other conditions. PPAR␥ full agonists, such as thiazolidinediones (TZDs), are effective insulin sensitizers and anti-inflammatory agents, but their use is limited by adverse side effects. Luteolin is a flavonoid with anti-inflammatory actions that binds PPAR␥ but, unlike TZDs, does not promote adipocyte differentiation. However, previous reports suggested variously that luteolin is a PPAR␥ agonist or an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 61 publications
5
64
0
7
Order By: Relevance
“…Structural studies have revealed that luteolin along with myristic acid occupies a ligand-binding pocket of PPAR␥ (35). The binding pocket occupied by luteolin is identical to that of the synthetic ligands thiazolidinediones, although each binding mode of PPAR␥ differs (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies have revealed that luteolin along with myristic acid occupies a ligand-binding pocket of PPAR␥ (35). The binding pocket occupied by luteolin is identical to that of the synthetic ligands thiazolidinediones, although each binding mode of PPAR␥ differs (35).…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies have revealed that luteolin along with myristic acid occupies a ligand-binding pocket of PPAR␥ (35). The binding pocket occupied by luteolin is identical to that of the synthetic ligands thiazolidinediones, although each binding mode of PPAR␥ differs (35). The x-ray crystal structure studies using purified recombinant HNF4␣ protein revealed that the ligand-binding pocket of HNF4␣ contains a mixture of fatty acids, including lauric, myristic, and palmitic acids (36).…”
Section: Discussionmentioning
confidence: 99%
“…23) From analysis of the crystal structure of the PPARγ LBD, luteolin (5,7,3′,4′-tetrahydroxyflavone) in these compounds occupies a buried ligand-binding pocket of PPARγ but binds an inactive PPARγ LBD conformer and occupies a space near the β-sheet region far from the activation helix. 24) On the basis of our results on the additive effects and noncompetitive reactions with a thiazolidinedione derivative, we presumed that H7-OG and H3′-OG did not bind to PPARγ in the same manner as thiazolidinedione derivatives.…”
Section: Discussionmentioning
confidence: 82%
“…ЛТ обладает слабой активностью частичного агониста/антагониста, ингибирует некоторые гены-мишени РАППg и РАППg-зависимый адипогенез [5], но подобно розиглитазону активирует транспортер глюкозы GLUT4, что подразумевает ген-специфический частичный агонизм [6]. Считается, что ЛТ может быть полезным для разработки безопасных селективных модуляторов РАППg [5,6,18].…”
Section: действие на сигнальные пути рецепторов-активаторов пролифераunclassified